Novel insights into the anatomy and histopathology of the sacroiliac joint and correlations with imaging signs of sacroiliitis in case of axial spondyloarthritis - Prati, Clément; Lequerre, Thierry; Le Goff, Benoît; Cortet, Bernard; Toumi, Hechmi; Tournadre, Anne; Marotte, Hubert; Lespessailles, Eric (Frontiers in Physiology, 2023)
For a better understanding of the pathophysiology of spondyloarthropathy (SpA), a detailed anatomical description of the sacroiliac joint is required because sacroiliitis is the earliest and most common sign of SpA and an essential feature for the diagnosis of ankylosing spondylitis. Beyond the anatomy, the histopathology of sacroiliac entheses and immunological mechanisms involved in sacroiliitis are crucial for a better understanding of disease causation. In this narrative review, we discuss the core anatomical, histological, and immunohistological observations involved in the development of sacroiliitis, focusing particularly on imaging-based information associated with sacroiliitis. Finally, we try to answer the question of whether at the sacroiliac joint, enthesitis precedes synovitis and subchondral bone changes in SpA.